Structural and functional characterization of flavivirus non-structural protein 3 (NS3) in solution and atomic and enzymatic insights of vancomysin resistant enterococcus faecalis (V583) alkyl hydroperoxide subunit C - Pan, Ankita (2018)
This thesis focuses on the non-structural protein 3 (NS3) of two flaviviral pathogens, the Dengue (DENV; DENV-2) and Zika virus (ZIKV), that have emerged as a major health concern in Singapore and world-wide. The NS3 comprises of an N-terminal serine protease domain and a C-terminal helicase domain which has nucleotide triphosphatase activities that are essential for RNA replication. NS3 is in constant motion and possess inherent flexibility. The inter- and intra-ensemble formation and crosstalk between the catalytically active helicase and protease require structural alterations and dynamic properties of the enzyme, allowing the catalytic centres to come in proximity during the enzymatic events. The first chapter of this thesis describes the flexibility of DENV-2 NS3 in solution based on small angle X-ray scattering (SAXS) experiments. The data reveal that the overall structure of DENV-2 NS3 is extended and flexible in solution. Using the ensemble optimization method (EOM) it is demonstrated that NS3 is capable of existing in different conformations in solution. In this context, the importance of the linker residues in flexibility and domain–domain arrangement is shown by the compactness of the individual protease and helicase domains. A 174PPAVP179 linker stretch of the related Hepatitis C virus (HCV) NS3 was swapped into DENV-2 NS3 by mutagenesis to investigate the effect of this ‘PPxxP’ linker motif in the compaction of the molecule. In addition, the overall low-resolution structure of the entire French Polynesia ZIKV NS3 in solution is presented for the first time. SAXS data of the entire ZIKV NS3 enabled rigid body modelling of the protein, which in turn sheds light on the domain-domain arrangement of the protein in solution. Solution studies of the individual protease and helicase domains show the compactness of the two domains as well as the contribution of the 10-residues linker region to the flexibility of NS3. Genetically engineered linker mutants of French Polynesia ZIKV NS3 enabled to identify linker residues being critical for the stability of the enzyme. Enzymatic characterization of both DENV- and ZIKV NS3 as well as its helicase domain provide insight into contribution of the individual NS3 domains. Finally, the inhibitory effect of ATPase inhibitors on the enzymatically active DENV-2 and ZIKV NS3 are provided. The second chapter of the thesis covers the structural and mechanistic aspects of the alkyl hydroperoxide reductase C of Enteroccoccus faecalis (EfAhpC) which together with subunit AhpF, a two-domain enzyme connected by a 41-residues linker, forms the so-called alkyl hydroperoxide reductase complex (AhpR), which is of paramount importance to restore redox homeostasis within the parasite. AhpCs are proposed to form enzymatically active homo-dimers and higher-oligomers. Such formations require flexibility and rearrangements of its C-terminal segment to come in proximity to the N-terminal segment of the second AhpC molecule, and to finally form a catalytic centre. In order to understand the dynamics and cross-talk of these enzymatic key segments of EfAhpC as well as the driving force(s) which modulates the equilibrium of dimer to higher oligomer formation, the first crystallographic structure of the E. faecalis AhpC (EfAhpC) was determined at 2.8 Å resolution, revealing a decamer-ring formed by five EfAhpC-dimers. The reported crystal structure provides insight into a transition state between a fully folded and locally unfolded conformation at the active site of the enzyme due to redox modulation. Amino acid substitutions of residues in the N- and C-termini as well as the oligomeric interphase of EfAhpC provide information into their structural and enzymatic roles. Mutagenesis, enzymatic and biophysical studies demonstrate the effect of the unusual existence of four cysteines in EfAhpC, which might optimize the functional adaptation of the E. faecalis enzyme under various physiological conditions.